2016
DOI: 10.1074/jbc.m116.738047
|View full text |Cite
|
Sign up to set email alerts
|

The A-Kinase Anchoring Protein (AKAP) Glycogen Synthase Kinase 3β Interaction Protein (GSKIP) Regulates β-Catenin through Its Interactions with Both Protein Kinase A (PKA) and GSK3β

Abstract: The A-kinase anchoring protein (AKAP) GSK3␤ interaction protein (GSKIP) is a cytosolic scaffolding protein binding protein kinase A (PKA) and glycogen synthase kinase 3␤ (GSK3␤). Here we show that both the AKAP function of GSKIP, i.e. its direct interaction with PKA, and its direct interaction with GSK3␤ are required for the regulation of ␤-catenin and thus Wnt signaling. A cytoplasmic destruction complex targets ␤-catenin for degradation and thus prevents Wnt signaling. Wnt signals cause ␤-catenin accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…In line with our results, it has previously been shown that PKA, upon stimulation of NIH-3T3 and HEK293 cells with ISO, can inactive GSK3α and GSK3β by phosphorylation at Ser21 and Ser9, respectively 31 . Similarly, it was recently shown that the GSK3 interaction protein, GSKIP, facilitates the phosphorylation of GSK3 by PKA at Ser9 and Ser21 and thereby its inhibition in HEK293 cells 47 . Therefore, it seems likely that GSK3 inactivation following ISO stimulation of brown adipocytes is also a direct consequence of PKA phosphorylation.…”
Section: Discussionmentioning
confidence: 87%
“…In line with our results, it has previously been shown that PKA, upon stimulation of NIH-3T3 and HEK293 cells with ISO, can inactive GSK3α and GSK3β by phosphorylation at Ser21 and Ser9, respectively 31 . Similarly, it was recently shown that the GSK3 interaction protein, GSKIP, facilitates the phosphorylation of GSK3 by PKA at Ser9 and Ser21 and thereby its inhibition in HEK293 cells 47 . Therefore, it seems likely that GSK3 inactivation following ISO stimulation of brown adipocytes is also a direct consequence of PKA phosphorylation.…”
Section: Discussionmentioning
confidence: 87%
“…Using bioinformatics tools, we identified several additional predicted targets of miR30a-5p, miR191-5p, miR195-5p and miR206-3p, all of which are expressed in the CNS (Table 1). For example, miR30a-5p is predicted to target GSKIP, a GSK3-beta and PKA scaffolding protein (Dema et al, 2016), and Rasd1, a member of the small G proteins, that plays a role in circadian rhythm (Cheng et al, 2006). miR191-5p is predicted to target actin and microtubules binding proteins including tropomodulin 2 which has been associated with synaptic plasticity and memory (Cox et al, 2003;Omotade et al, 2018).…”
Section: Micrornas Targeting Bdnf Are Upregulated Only In Rapid Onsetmentioning
confidence: 99%
“…The results of this study show that knockout of Prdx2 in DMSCs can reduce the activity of GSK3β and promote the translocation of β-catenin into the nucleus, thereby activating the downstream signaling pathways. However, activation of this signaling pathway did not improve cell proliferation caused by PRDX2 knockout, high expression of cyclin D1 also did not prevent cell-cycle arrest (40).The kinase activity of GSK3β can be regulated by different signaling pathways, in which phosphorylated AKT can phosphorylate GSK3β to inactivate it (12,37,41). In Prdx2 -/-DMSCs, the phosphorylation of AKT increased as the number of cell passages increased, this is most likely achieved through cross talk between the PRDX2, PDGF and PI3K signals (42).…”
Section: Discussionmentioning
confidence: 99%